Spooky Integrals

Calculus Level 5

Given k = 1 3 [ 0 x k 4 e ( k + 1 ) 4 x d x ] = a b π c d , \prod_{k=1}^3\left[\int_0^\infty x^{-\frac{k}{4}}e^{-(k+1)^4x}\;dx\right]=\frac{\sqrt{a}}{b}\pi^{\frac{c}{d}}, what is the value of a + b + c + d ? a+b+c+d?


The answer is 295.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Tunk-Fey Ariawan
Mar 30, 2014

These integrals can be solved fairly straightforward by using gamma function properties.

For k = 1 k=1 , we have 0 x 1 4 e 16 x d x = 1 8 0 u 1 4 e u d u = 1 8 Γ ( 3 4 ) , u = 16 x . \int_0^\infty x^{-\frac{1}{4}}e^{-16x}\;dx=\frac{1}{8}\int_0^\infty u^{-\frac{1}{4}}e^{-u}\;du=\frac{1}{8}\Gamma\left(\frac{3}{4}\right),\quad\Rightarrow\quad u=16x. For k = 2 k=2 , we have 0 x 1 2 e 81 x d x = 1 9 0 v 1 2 e v d v = 1 9 Γ ( 1 2 ) , v = 81 x . \int_0^\infty x^{-\frac{1}{2}}e^{-81x}\;dx=\frac{1}{9}\int_0^\infty v^{-\frac{1}{2}}e^{-v}\;dv=\frac{1}{9}\Gamma\left(\frac{1}{2}\right),\quad\Rightarrow\quad v=81x. For k = 3 k=3 , we have 0 x 3 4 e 256 x d x = 1 4 0 w 3 4 e w d w = 1 4 Γ ( 1 4 ) , w = 256 x . \int_0^\infty x^{-\frac{3}{4}}e^{-256x}\;dx=\frac{1}{4}\int_0^\infty w^{-\frac{3}{4}}e^{-w}\;dw=\frac{1}{4}\Gamma\left(\frac{1}{4}\right),\quad\Rightarrow\quad w=256x. Therefore k = 1 3 [ 0 x k 4 e ( k + 1 ) 4 x d x ] = 1 8 Γ ( 3 4 ) 1 9 Γ ( 1 2 ) 1 4 Γ ( 1 4 ) = 1 9 Γ ( 1 2 ) 1 8 Γ ( 3 4 ) 1 4 Γ ( 1 4 ) . \begin{aligned} \prod_{k=1}^3\left[\int_0^\infty x^{-\frac{k}{4}}e^{-(k+1)^4x}\;dx\right] &=\frac{1}{8}\Gamma\left(\frac{3}{4}\right)\cdot\frac{1}{9}\Gamma\left(\frac{1}{2}\right)\cdot\frac{1}{4}\Gamma\left(\frac{1}{4}\right)\\ &=\frac{1}{9}\Gamma\left(\frac{1}{2}\right)\cdot\frac{1}{8}\Gamma\left(\frac{3}{4}\right)\cdot\frac{1}{4}\Gamma\left(\frac{1}{4}\right).\\ \end{aligned} Note that : Γ ( 1 2 ) = π \Gamma\left(\frac{1}{2}\right)=\sqrt{\pi} and from Euler's reflection formula , we have Γ ( x ) Γ ( 1 x ) = π sin ( π x ) . \Gamma(x)\Gamma(1-x)=\frac{\pi}{\sin(\pi x)}. Hence, k = 1 3 [ 0 x k 4 e ( k + 1 ) 4 x d x ] = 1 9 π 1 8 Γ ( 1 1 4 ) 1 4 Γ ( 1 4 ) = 1 288 π π sin ( 1 4 π ) = 2 288 π 3 2 . \begin{aligned} \prod_{k=1}^3\left[\int_0^\infty x^{-\frac{k}{4}}e^{-(k+1)^4x}\;dx\right] &=\frac{1}{9}\sqrt{\pi}\cdot\frac{1}{8}\Gamma\left(1-\frac{1}{4}\right)\cdot\frac{1}{4}\Gamma\left(\frac{1}{4}\right)\\ &=\frac{1}{288}\sqrt{\pi}\cdot\frac{\pi}{\sin\left(\frac{1}{4}\pi\right)}\\ &=\frac{\sqrt{2}}{288}\pi^{\frac{3}{2}}. \end{aligned} Thus, a + b + c + d = 2 + 288 + 3 + 2 = 295 a+b+c+d=2+288+3+2=\boxed{\color{#3D99F6}{295}} .


# Q . E . D . # \text{\# }\mathbb{Q.E.D.}\text{ \#}

an easy prblm

science beginner - 7 years ago

Well, written. Kudos!

Himanshu Arora - 6 years, 11 months ago
Aditya Kumar
Jan 20, 2016

Alternate Solution:

Let, I = 0 x k 4 e ( k + 1 ) 4 x d x = M { e ( k + 1 ) 4 x } ( 1 k 4 ) I=\int _{ 0 }^{ \infty } x^{ -\frac { k }{ 4 } }e^{ -(k+1)^{ 4 }x }\; dx\\ =M\left\{ e^{ -(k+1)^{ 4 }x } \right\} \left( 1-\frac { k }{ 4 } \right)

Here M{f(x)}(s) is Mellin transform of f(x) over s.

Now using Maclaurin series, e ( k + 1 ) 4 x = n = 0 ( k + 1 ) 4 n n ! ( x ) n e^{ -(k+1)^{ 4 }x }=\sum _{ n=0 }^{ \infty }{ \frac { -(k+1)^{ 4n } }{ n! } { \left( -x \right) }^{ n } }

Therefore, by Ramanujan's Master Theorem , I = ( k + 1 ) k 4 Γ ( 1 k 4 ) I={ \left( k+1 \right) }^{ k-4 }\Gamma \left( 1-\frac { k }{ 4 } \right)

Now taking the product we get: k = 1 3 [ 0 x k 4 e ( k + 1 ) 4 x d x ] = 2 288 π 3 2 \prod _{ k=1 }^{ 3 } \left[ \int _{ 0 }^{ \infty } x^{ -\frac { k }{ 4 } }e^{ -(k+1)^{ 4 }x }\; dx \right] =\frac { \sqrt { 2 } }{ 288 } \pi ^{ \frac { 3 }{ 2 } }

@Pi Han Goh another one!

Aditya Kumar - 5 years, 4 months ago
Aaghaz Mahajan
May 17, 2018

Gamma functions and Euler's Reflection Formula!!!!!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...